Swelling Behaviours of Silk Fibroin-Polyurethane Composite Hydrogels - Chen, Guangmei; Liu, Chao; Zhang, Baoping; Xu, Gewen; Huang, Yiping (Asian Journal of Chemistry, 2014)
Silk fibroin-polyurethane (SF-PU) hydrogels with different SF/PU ratios were fabricated. FTIR was applied to characterize the structure of the hydrogels. It was found that cross-linked network formed through chemical reactions between -NCO groups on the PU chain and -NH2, -OH groups on the SF chains, in addition to the hydrogen bonding interactions. SEM was taken to observe the morphology of hydrogels exhibited a porous structure. The swelling ratio of hydrogel could be as high as 4.37 and it decreased with the increase of SF contents. Due to that the diffusion exponent (n) was about 0.45, the initial swelling stages were thought to be controlled by the Fickian diffusion. For the whole swelling process, experimental results well fitted into the Schott second-order kinetic equation.